If it's not what You are looking for type in the equation solver your own equation and let us solve it.
+9=6K(K-11)
We move all terms to the left:
+9-(6K(K-11))=0
We calculate terms in parentheses: -(6K(K-11)), so:We get rid of parentheses
6K(K-11)
We multiply parentheses
6K^2-66K
Back to the equation:
-(6K^2-66K)
-6K^2+66K+9=0
a = -6; b = 66; c = +9;
Δ = b2-4ac
Δ = 662-4·(-6)·9
Δ = 4572
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$K_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$K_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{4572}=\sqrt{36*127}=\sqrt{36}*\sqrt{127}=6\sqrt{127}$$K_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(66)-6\sqrt{127}}{2*-6}=\frac{-66-6\sqrt{127}}{-12} $$K_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(66)+6\sqrt{127}}{2*-6}=\frac{-66+6\sqrt{127}}{-12} $
| 2x+34.4=200 | | 5d-9=-4 | | 5.5x+2/3x=37 | | 3x^2-42x+99=0 | | (3/x)+3=(3/5x)+(31/10) | | 3x^2+18x-273=0 | | 13=r/20 | | 4r-2r=20 | | 8w-7w=20 | | 2x^2−36x+34=0 | | 10*115=x*x | | 14x-12=14x+12 | | 80-2x=98 | | F(-5)=-3x-1 | | 10*115=2x | | -1.9c=7.6 | | -6(n+8)=2(1-3n)+5n | | 5x–20+3x–9x=-12x+30+8x | | -2x^2+16x-194=0 | | 10*18=12*x | | 5(3x-20=-10 | | 4=-4w+2(w-2) | | 10*8=12*x | | 7-2xx=-2 | | -2x^2+32x-290=0 | | 20=k/17 | | 4×(8-3a)=-2×(2+3a)+12 | | -8(v+-5)=-6v-20 | | 370=15n+85 | | 3z/2=2/6+4 | | f(-3,16)=-3,16^4-5(-3,16)^2+4 | | 2x+6=2(x+3 |